PERSPEKTIF IPS TERHADAP MBG: MEMBANGUN KESADARAN SOSIAL DAN KETAHANAN PANGAN SISWA SD - Linda Salsa Linda (FKIP Universitas Wiraraja, 2026)
The MBG program is a national intervention aimed at improving the nutritional intake of students while building food security. From an IPS education perspective, few studies have linked the MBG program to the formation of social behavior. The purpose of this study is to analyze how IPS education can support the implementation of MBG in the context of elementary schools. The research method used is SLR with PRISMA guidelines. The search was conducted on Google Scholar, ScienceDirect, and ERIC using a combination of keywords related to nutrition, social studies education, and food security. Of the 214 articles identified, 94 articles met the inclusion criteria. The SLR results showed three thematic findings: (1) MBG had a positive impact on students' learning motivation, concentration, and nutritional status; (2) social studies learning had strong points of convergence with food security issues, thus having the potential to build social awareness; (3) limited implementation in terms of cross-sector coordination, school nutrition literacy, and social value integration. This study scientifically offers a conceptual framework of how social studies education can become a support system for strengthening the MBG program with active learning based on food security.